2020
DOI: 10.30762/mediakita.v4i1.2444
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Peran Media Dalam Upaya Pencegahan Penyebaran Virus Corona (Covid-19) Di Indonesia

Abstract: The media has a very an important role in the lives of Indonesian. Some of news as a public comsumption, including corona virus. The information is necessary for in- dept analysis related how the role of media for people on the issue of the virus corona.   This research uses a mixed method, by distributing Google forms and by phone interviews to people who live in 6 provinces which have a total of 50 cases exposed to the corona virus in Indonesia, including DKI Jakarta, East Java, Central Java, West Java, Bant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
2
0
4
Order By: Relevance
“…Based on the research from Adawiyah and Kadir (2020), it is said that the influence of media has a significant influence on community life, especially digital media which is currently widely used to find out information about the coronavirus ranging from the type of virus to ways and efforts in avoiding the coronavirus outbreak. From the results of research examined by researchers, it was found that study participants of the male and female sexes spread across their 6 provinces had the same point of view about the importance of conducting health campaigns about this pandemic through digital media.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the research from Adawiyah and Kadir (2020), it is said that the influence of media has a significant influence on community life, especially digital media which is currently widely used to find out information about the coronavirus ranging from the type of virus to ways and efforts in avoiding the coronavirus outbreak. From the results of research examined by researchers, it was found that study participants of the male and female sexes spread across their 6 provinces had the same point of view about the importance of conducting health campaigns about this pandemic through digital media.…”
Section: Resultsmentioning
confidence: 99%
“…Pada saat memasuki tahun ajaran baru ternyata pandemic covid 19 covid 19 belum juga berlalu, pemerintah menganjurkan tetap melakukan pembelajaran dari rumah. Sehingga awal tahun ajaran baru pertengahan bulan Juli 2020 dilakukan pembelajaran kombinasi daring dan luring jadi pilihan, namun hasilnya masih belum memuaskan karena masih banyak peserta didik yang tidak aktif dalam pembelajaran dan tidak mengumpulkan tugas dengan alasan sinyal, paket internet, tidak punya HP dan sebagainya (Adawiyah & Kadir, 2020).…”
Section: B Pembahasan 1 Paparan Data Pra Tindakanunclassified
“…Dimasa pandemik, adanya kebijakan social distancing dari pemerintah yang mengharuskan segala aktifitas dilakukan dirumah, sehingga sebagian besar waktu dihabiskan bersama kelaurga dan teman (11). Beberapa hasil studi, melaporkan faktor dukungan keluarga sebagai unit terkecil dalam lingkungan sosial memiliki hubungan dengan perilaku pencegahan Covid-19 (12)(13)(14).…”
Section: Pendahuluanunclassified